Vitamins and micronutrients in children with chronic kidney diseases - F. I. Rusnak (Лечащий Врач, 2023)
Chronic kidney diseases (CKD) in children of our country develop against the background of hypovitaminosis, characteristic of the child population. Both in our and foreign studies, vitamin D deficiency is noted in children with CKD. However, the decrease in vitamin D in the blood depends on the nosological unit that underlies the development of CKD. In tubulointerstitial kidney diseases, which are mainly characterized by slow progression of CKD, vitamin D deficiency is less significant. In children with glomerulonephritis, especially when using glucocorticoids, vitmin D deficiency and phosphorus-calcium disorders are more pronounced. The concomitant probable deficiency of vitamins C, B2, B6, E, K, folic acid further aggravates the metabolism of vitamin D and its reception system, requires research to clarify the degree of hypovitaminosis among children with CKD and those on renal replacement therapy. Hypervitaminosis A is observed already in the early stages of CKD due to a slowdown in the excretion of retinoids by the kidneys, and its levels are highest in children receiving supplemental nutrition containing vitamin A, compared with diet alone. Increased retinoids in the blood serum significantly predetermine the development of hypercalcemia. When using multivitamin preparations in children with CKD, a differentiated approach is necessary, preferably justified by the preliminary determination of vitamins in the blood.